Improving the Biomass Energy Yield of Cocksfoot Cultivated on Degraded Soil Amended with Organic–Mineral Fertilizer - Urszula Wydro; Elżbieta Wołejko; Jolanta Joniec; Agata Bober; Mariola Chomczyńska (Energies)
The current difficult political and economic situation generates the need to seek new sources of energy, and the solution may be to increase biomass of energy crops through using organic–mineral wastes to improve soil quality. The research objectives were to determine the effect of coal gangue (CG) and sewage sludge (SS) based organic–mineral fertilizer (OMF) application on cocksfoot growth and subsequently on biogas and methane production. First, a 6-week vegetation experiment was conducted where degraded soil (DS) taken from the edge of a sand mine in Rokitno was amended with OMF at 1% (DS + 1), 2%, 5%, and 10%. Cocksfoot was sown on such prepared soils. At the end of the first stage of the experiment, plant and soil samples were collected. In cocksfoot, dry shoot and root biomass were determined. The main soil properties and soil dehydrogenases, alkaline phosphatase (ALP), acid phosphatase (ACP), and protease (PROT) activities were analyzed. Next, an anaerobic fermentation experiment was conducted. In batch assay of digestion, cocksfoot collected from arable soil (CS) and from DS + 1% was used. Concerning the pot experiment, there was higher PROT in DS + 5% (by 133%) and DS + 10% (by 417%) compared to CS, and ALP in DS + 10% was higher by 19% than in CS. Shoot dry matter in OMF-amended DS was 107–297% higher than in CS. Among the fermentation experiment, the greatest differences (20–37%) in average daily biogas production between CS and DS + 1% were observed at 2–4 days but methane content in biogas in both variants was similar. Summarizing, fertilizer based on SS and CG can be a valuable substrate for degraded soil and increase in energy crops biomass.